The courage to face yourself: About being a social worker in an unknown culture and in unfamiliar situations (Journal of Comparative Social Work, 2011)
I have called this essay, The courage to face yourself; in it, I use stories from my internship in Cuba to reflect on being a Norwegian social worker in another country. I also consider the many challenges that arise in this situation, and focus on the two different cultures and their attendant values, norms and morals. The stories are also about being a social worker in an unfamiliar culture and being in new situations. They are about the importance of getting to know yourself, daring to fully face yourself and having the courage to be the person you want to be, both privately and professionally. They are about developing yourself through interactions with others. They are about giving voice to the uncomfortable and incomprehensible. They are about having the courage to be yourself.